Comparative efficacy of conventional vs new chemistry insecticides against mango thrips, scirtothrips dorsalis hood (Thripidae: Thysanoptera) - Haider Karar; Muhammad Umar Javed; Muhammad Yaseen; Muhammad Amjad Bashir; Asif Sajjad; Muhammad Essa; Muhammad Wajid; Muhammad Mubashir; Ghulam Mustafa; Muhammad Zubair; Salwa Alreshaidan; Sagheer Atta; et al. (Journal of King Saud University: Science, 2022)
Thirteen insecticides- Stake 40WV (triazophos), Polo 500SC (diafenthiuron), Actara 25WG (thiamethoxam), Chlorfenapyr 36SC (chlorfenapyr), Maximal 60WG (nitenpyram + pymetrozine), Crown 20SL, Lescenta 80WG (fipronil + imidacloprid), Fyfanon 57EC (malathion), Talstar 10EC (bifenthrin) Momentum 50WG (nitenpyram + chlorfenapyr), Jozer 202SL (imidacloprid + acetamaprid), Tresta 20SC (clothianidin) and Closer 240SC (sulfoxaflor)- were evaluated for efficacy in a controlled mango nursery experiment against an active infestation of Scirtothrips dorsalis at the Mango Research Institute, Multan during 2018 and 2019. The data was recorded before the treatments were applied, then 24, 72, 168 h after treatment. Treatments with percent mortality greater than 70 % were considered to be effective controls. Percent mortality was 74.14 % for chlorfenapyr, 70.58 % for Momentum, and 70.51 % for Crown at post-treatment on an cumulative average of 24, 72 and 168 h of both the study years. Medium percent mortality was; 69.52 % for Jazor; 59.59 % for Maximal; 57.38 % for Actara; and 45.11 for Lescenta. All other treatments had percent mortality estimates of less than 30 %. It is concluded that chlorfenapyr, Momentum and Crown are suggested to be used on mango nursery against S. dorsalis for better management since among the treatments in the trial efficacious control was found at 24, 72 and 168 h post-treatment.